THE USE OF AI-BASED WRITING TOOLS (QUILLBOT AND CHATGPT) IN DEVELOPING THE WRITING COMPETENCE OF LANGUAGE LEARNERS - Suharto, Ririn Pratiwi; Zubaidi; Nurdjizah; Putri, Aulia Nourma; Putri Sekarsari (Universitas PGRI Palembang, 2025)
The study explored the impact of AI-based writing tools, namely QuillBot and ChatGPT, on enhancing the writing competence of students enrolled in the English for Business Writing course within the D4 Marketing Management program at Politeknik Negeri Malang. Employing a descriptive qualitative approach, data were collected through a series of pre-tests and post-tests to assess changes in students’ writing performance. The findings demonstrated a marked improvement across various writing components, with average scores consistently exceeding 3.0. ChatGPT played a pivotal role in facilitating idea generation and structuring written texts, while QuillBot proved effective in refining grammatical accuracy, spelling, and vocabulary usage. When used in tandem, these tools significantly improved the content quality, coherence, and overall organization of students' writing. The study recommends the sustained integration of these AI-powered applications alongside systematic writing practice and constructive teacher feedback. Moreover, it offers practical insights for language educators seeking to leverage artificial intelligence to support and enhance learners' writing development.